Magnesium to counteract elastin degradation and vascular calcification in chronic obstructive pulmonary disease. (September 2017) - Janssen, Rob
Abstract: Accelerated elastin degradation is an important pathogenic mechanism in chronic obstructive pulmonary disease (COPD) leading to irreversible lung function loss and cardiovascular comorbidities. The rate of elastin breakdown is a predictor of mortality in patients with COPD. Decelerating elastinolysis might be an attractive therapeutic target in this debilitating condition. Vascular calcification starts in the elastin network of the arterial wall and is enhanced in patients with COPD. Elastin calcification is accompanied by an upregulation of matrix metalloproteinase gene expression and consequently a shift in the elastase/anti-elastase balance towards degradation. Magnesium can be regarded as a natural calcium antagonist and has the proven ability to ameliorate vascular calcification. Furthermore, an animal study has suggested that magnesium deficiency promotes elastin degradation. I hypothesize that inhibiting elastin calcification by means of magnesium supplementation might counteract both vascular calcification and elastin degradation in COPD. This could potentially have a favorable impact on cardiovascular and respiratory related morbidity/mortality in patients with COPD.